Instructional design and development process of a virtual reality (VR)-based system for learning basic photocopying procedures - Ting, Lee Yi (Universiti Malaysia Sarawak, UNIMAS, 2009)
This project focuses on the instructional design and development process of a desktop virtual reality (VR)–based learning system. This learning system is meant to facilitate novice photocopier users in learning its basic procedures via the use of a virtual threedimensional (3D) photocopier. This project elaborates on how the learning system was designed and developed based on an instructional design theoretical framework and an instructional development model. It also described the design and development process of the various components of the learning system such as its surface design, interface design, scenario, instructional strategies and language. These components evolved from the single path prototype to alpha version and finally, beta version which was packaged. The design and development process involved experts and learners who provided feedback to improve the learning system. Three principles, (i) recursion or non-linearity principle; (ii) reflection principle; and (iii) participatory design were used to guide the design and development process. This project also suggested some recommendations and future works to improve the learning system.